Carboxylate Ion Pairing with Alkali-Metal Ions for β-Lactoglobulin and Its Role on Aggregation and Interfacial Adsorption - Beierlein, Frank; Clark, Timothy; Braunschweig, Björn; Engelhardt, Kathrin; Glas, Lena; Peukert, Wolfgang (Journal of Physical Chemistry B, 2015)
We report a combined experimental and computational study of the whey protein extgreekb-lactoglobulin (BLG) in different electrolyte solutions. Vibrational sum-frequency generation (SFG) and ellipsometry were used to investigate the molecular structure of BLG modified air-water interfaces as a function of LiCl, NaCl, and KCl concentrations. Molecular dynamics (MD) simulations and thermodynamic integration provided details of the ion pairing of protein surface residues with alkali-metal cations. Our results at pH 6.2 indicate that BLG at the air-water interface forms mono- and bilayers preferably at low and high ionic strength, respectively. Results from SFG spectroscopy and ellipsometry are consistent with intimate ion pairing of alkali-metal cations with aspartate and glutamate carboxylates, which is shown to be more effective for smaller cations (Li(+) and Na(+)). MD simulations show not only carboxylate-alkali-metal ion pairs but also ion multiplets with the alkali-metal ion in a bridging position between two or more carboxylates. Consequently, alkali-metal cations can bridge carboxylates not only within a monomer but also between monomers, thus providing an important dimerization mechanism between hydrophilic surface patches.
EAM Import::2019-03-13
Keywords: electrolyte; solution; molecular; dynamics; surface